Role of Intermediate Filaments in Blood–Brain Barrier in Health and Disease - Ece Bayir; Aylin Sendemir (Cells, 2021)
The blood–brain barrier (BBB) is a highly selective cellular monolayer unique to the microvasculature of the central nervous system (CNS), and it mediates the communication of the CNS with the rest of the body by regulating the passage of molecules into the CNS microenvironment. Limitation of passage of substances through the BBB is mainly due to tight junctions (TJ) and adherens junctions (AJ) between brain microvascular endothelial cells. The importance of actin filaments and microtubules in establishing and maintaining TJs and AJs has been indicated; however, recent studies have shown that intermediate filaments are also important in the formation and function of cell–cell junctions. The most common intermediate filament protein in endothelial cells is vimentin. Vimentin plays a role in blood–brain barrier permeability in both cell–cell and cell–matrix interactions by affecting the actin and microtubule reorganization and by binding directly to VE-cadherin or integrin proteins. The BBB permeability increases due to the formation of stress fibers and the disruption of VE–cadherin interactions between two neighboring cells in various diseases, disrupting the fiber network of intermediate filament vimentin in different ways. Intermediate filaments may be long ignored key targets in regulation of BBB permeability in health and disease.